Role of mGluR5 neurotransmission in reinstated cocaine‐seeking. (17th February 2012) - Wang, Xiusong; Moussawi, Khaled; Knackstedt, Lori; Shen, Haowei; Kalivas, Peter W.
ABSTRACT In animal models of addiction, reducing glutamate stimulation of the metabotropic glutamate receptor 5 (mGluR5) inhibits drug‐seeking. The present study used the reinstatement model of cocaine‐seeking to show that blockade of mGluR5 directly in the core subcompartment of the nucleus accumbens (NAcore) prevented both conditioned cue‐ and cocaine‐reinstated drug‐seeking. Consistent with this finding, microinjection of the mGluR5 agonist (RS)‐2‐chloro‐5‐hydroxyphenylglycine into the NAcore produced modest reinstatement of lever pressing when given alone and significantly potentiated cue‐induced reinstatement. Homer proteins are contained in the post‐synaptic density and regulate mGluR5 intracellular signaling and trafficking to the membrane. Microinjecting a membrane permeable peptide antagonist of Homer binding to mGluR5 into the NAcore also inhibited cue‐ and cocaine‐reinstated lever pressing. However, this peptide did not change the surface expression of mGluR5, indicating that the peptide inhibitor did not alter the surface trafficking of mGluR5. Taken together, these data show that mGluR5 inhibition and stimulation in the NAcore can regulate cocaine‐seeking, and demonstrate that one mechanism for this effect is via interactions with Homer proteins.